The Challenges of the Networked Enterprises: A Conceptual Paradigm - Mostéfaoui , Sofiane; Yousfat, Ali (Technium Social Sciences Journal, 2022)
This article attempts to examine the networked business as a partnership strategy in a very complicated competitive context. At first, we focus on the design, characteristics and the different strategic objectives undertaken by the forms of cooperation. The second part of the article is devoted to determine the decisive factors such as trust and transparency as well as shared interest adopted by the managers to build a sustainable partnership network.